2022
DOI: 10.1002/hipo.23479
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the CA2 region in the hippocampal network during epileptogenesis

Abstract: The CA2 pyramidal cells are mostly resistant to cell death in mesial temporal lobe epilepsy (MTLE) with hippocampal sclerosis, but they are aberrantly integrated into the epileptic hippocampal network via mossy fiber sprouting. Furthermore, they show increased excitability in vitro in hippocampal slices obtained from human MTLE specimens or animal epilepsy models. Although these changes promote CA2 to contribute to epileptic activity (EA) in vivo, the role of CA2 in the epileptic network within and beyond the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Recent evidence has supported a role for hippocampal area CA2 in modulating hippocampal network activity and seizure generation (Boehringer et al, 2017; Kilias et al, 2022; Whitebirch et al, 2022). Because RGS14 is highly and selectively expressed within area CA2 where it reduces neuronal excitability and inhibits long-term potentiation at CA3-CA2 excitatory synapses (Lee et al, 2010), we explored whether loss of RGS14 (RGS14 KO) altered hippocampal seizure activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence has supported a role for hippocampal area CA2 in modulating hippocampal network activity and seizure generation (Boehringer et al, 2017; Kilias et al, 2022; Whitebirch et al, 2022). Because RGS14 is highly and selectively expressed within area CA2 where it reduces neuronal excitability and inhibits long-term potentiation at CA3-CA2 excitatory synapses (Lee et al, 2010), we explored whether loss of RGS14 (RGS14 KO) altered hippocampal seizure activity.…”
Section: Resultsmentioning
confidence: 99%
“…Our group and others have shown that RGS14 is integral for area CA2 pyramidal cell (PC) signaling and function (Montanez-Miranda et al, 2022). Based on recent reports of the protective capacity of RGS14 in peripheral tissue (Li et al, 2016; Zhang et al, 2022) and the newly appreciated contribution of area CA2 in TLE (Freiman et al, 2021; Haussler et al, 2016; Kilias et al, 2022; Whitebirch et al, 2022; Wittner et al, 2009), we hypothesized that RGS14 may serve a protective role in area CA2 following seizure insult. Here, we show that loss of RGS14 sensitizes mice to the behavioral effects of KA-SE demonstrated by expedited entry into SE and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these mice have facilitated the study of CA2 in the context of seizures, as reported here in a research article by Häussler and colleagues (Kilias et al, 2023). Given CA2's position within the hippocampal circuit, and its apparent resistance to cellular injury (Leranth & Ribak, 1991;Sloviter et al, 1991), it is clear that CA2 likely plays a central role in the pathological activity seen in individuals with epilepsy and understanding that role will be critical in developing more effective treatment strategies (Boehringer et al, 2017;Häussler et al, 2016;Whitebirch et al, 2022).…”
mentioning
confidence: 88%
“…5 This resistance of the DG and CA2 neurons to neuronal loss in TLE has been proposed to make these areas critical to seizure propagation through the epileptic hippocampus. [6][7][8] However, relatively few studies have directly tested the idea that area CA2 regulates seizures in TLE.…”
Section: Introductionmentioning
confidence: 99%